2017
DOI: 10.1097/wnp.0000000000000396
|View full text |Cite
|
Sign up to set email alerts
|

Insular Epilepsy: Semiology and Noninvasive Investigations

Abstract: In this review, authors discuss the semiology and noninvasive investigations of insular epilepsy, an underrecognized type of epilepsy, which may mimic other focal epilepsies. In line with the various functions of the insula and its widespread network of connections, insular epilepsy may feature a variety of early ictal manifestations from somatosensory, visceral, olfactory, gustatory, or vestibular manifestations. Depending on propagation pathways, insular seizures may also include altered consciousness, dysto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 87 publications
3
28
0
Order By: Relevance
“…Because of the wealth of insular connections to surrounding lobes, the clinical manifestations of operculoinsular seizures are diverse (7,28). Therefore, the localization of the seizure onset zone in some cases can be quite difficult and this is also a major reason of some surgery failures (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the wealth of insular connections to surrounding lobes, the clinical manifestations of operculoinsular seizures are diverse (7,28). Therefore, the localization of the seizure onset zone in some cases can be quite difficult and this is also a major reason of some surgery failures (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Although operculoinsular epilepsy is relatively rare, it accounts for a non-negligible proportion of drug-resistant epilepsy surgical candidates and sometimes it can be difficult to be recognized (4)(5)(6). Because of the complex physiology and the rich connections to surrounding and remote structures, the clinical manifestations of operculoinsular seizures can be diverse (7). It is reported that operculoinsular epilepsy can have semiology similar to temporal lobe seizures, frontal lobe seizures or parietal lobe seizures (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic defects have been reported in operculo-insular epilepsy cases, including mutations in the CHRNB2 and CHRNA4 genes in 2 patients with sleep-related hypermotor seizures (functional testing under way). 24 A subtle insular focal cortical dysplasia was reported in a patient with familial focal epilepsy associated with DEPDC5 mutation. 25 Finally, Nguyen and colleagues 26 described an epileptogenic network involving the temporo-insular region in a family with reflex bathing epilepsy associated with a Q555X mutation of synapsin 1 on chromosome Xp11-q21.…”
Section: Noninvasive Investigation Of Operculo-insular Epilepsymentioning
confidence: 98%
“…The wide spectrum of insular connectivity-related functions accounts for the diverse ictal manifestations observed in operculo-insular epilepsy (OIE). Insular seizures may present with various seizure manifestations including visceral, affective, autonomic and sensory auras, motor and non-motor seizure types that can mimic parietal, frontal or temporal lobe seizures and render the clinical recognition of OIE arduous ( Nguyen et al, 2009 ; Obaid et al, 2017 ). Moreover, non-invasive electrophysiological and imaging investigations including scalp electroencephalography (sEEG), ictal single-photon emission computed tomography (SPECT), positron emission tomography (PET) often fail to reveal the precise epileptic origin, eventually requiring invasive EEG monitoring to confirm the location of the epileptic focus ( Gras-Combe et al, 2016 ; Isnard et al, 2000 ; Mohamed et al, 2013 ; Ostrowsky et al, 2000 ; Ryvlin et al, 2006 ; Weil et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For those reasons, OIE remains a diagnostic challenge and probably under-recognized condition. In patients with drug-resistant OIE epilepsy, accurate identification may lead to successful epilepsy surgery while failure to recognize it may lead to resection of the wrong area and poor post-operative seizure outcome( Nguyen et al, 2009 ; Obaid et al, 2017 ; Surbeck et al, 2010 ; Alomar et al, 2017 ; Bouthillier and Nguyen, 2017 ; Freri et al, 2017 ; Malak et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%